ICTforAg 2024: Virtual day session. Monitoring food security trends in digital spaces: A multi-platform approach to nowcast food insecurity - Carneiro, Bia; Tucci, Giulia; Resce, Giuliano; Johnson, Kiersten; Caravaggio, Nicola (2024)
Given the growing significance of internet-based information flows, the digital innovations team at CGIAR FOCUS Climate Security has developed an approach that integrates digital platforms to nowcast social phenomena, applied to the context of food security monitoring in the Global South. In this session, we will present our framework and a pilot interactive dashboard, in which users can access high level trends, as well as the original content driving insights. We will also reflect on the implications and utility of digital platforms analysis to food insecurity early warning.